Contribuição de perfilhos aéreos e basais na dinâmica de produção de forragem do capim-braquiária após o pastejo diferido - Santos, Manoel Eduardo Rozalino; e Castro, Marina Reis Sant'Anna; Gouvêia, Sabrina Carraro; Gomes, Virgilio Mesquita; Da Fonseca, Dilermando Miranda; Santana, Sabrina Saraiva [UNESP] (My University, 2014)
During the spring, the understanding of regrowth in basal and aerial tillers of deferred pasture in winter it is necessary. Thus, the objective was to evaluate the morphogenesis and herbage accumulation during spring in Brachiaria decumbens cv. Basilisk (signalgrass) pasture used under deferred grazing in winter. The basal and aerial tillers in same pasture were evaluated. The signalgrass was managed with grazing cattle and with an average height of 25 cm. The randomized block design with three replications was adopted. The leaf appearance rate, phyllochron and the numbers of expanded, expanding and live leaves did not differ between basal and aerial tillers. The aerial tiller possessed lower rates of leaf senescence, of leaf elongation and of stem elongation, as well as lower number of dead leaf and stem and leaf lamina lengths, compared to basal tiller. The leaf lifespan was higher in aerial tillers than at basal. The basal tiller also contributed to higher rates of tissue growth and forage accumulation in pasture when compared to aerial tiller. After deferred grazing during the spring, the aerial tiller has low participation in forage production of signalgrass pasture.
Contribution of basal and aerial tillers in dynamics of herbage production of signalgrass after grazing deferred
Keywords: Brachiaria decumbens; Forage accumulation; Grazing; Leaf; Senescence; Stem